Linguacultural Aspects of English Dramas - Samatova Shaxzoda (Scientific Trends, 2025)
This article examines the linguacultural dimensions of English dramas through the analysis of dramatic dialogue, cultural symbolism, and linguistically encoded social norms. By exploring examples from Shakespeare, Shaw, Wilde, Pinter, and Delaney, the study demonstrates how dramatic language reflects cultural identity, social hierarchy, communicative strategies, and worldview. The inclusion of direct quotations from the plays highlights how linguistic forms embody historical and cultural meanings. The article concludes that English drama provides a rich foundation for understanding the interaction between language and culture, and serves as an important resource for developing intercultural competence.
Keywords: Linguaculture, English drama, cultural identity, discourse, pragmatics, stylistics, dramatic dialogue.